Cardiogenic shock due to coronary artery disease associated with interrupted aortic arch - Luís Alberto Oliveira Dallan (Revista Brasileira de Cirurgia Cardiovascular/Brazilian Journal of Cardiovascular Surgery, 2013)
Acute pulmonary edema is a serious event. Its occurrence in association with interrupted aortic arch and coronary heart disease is rare. Recently, an old patient developed cardiogenic shock and acute pulmonary edema due to acute coronary insuf - ficiency, associated with interrupted aortic arch. The coronary angiography revealed occlusion of the right coronary artery and 95% obstruction in the left main coronary artery, associ - ated with interruption of the descending aorta. Coronary artery bypass graft was performed, without extracorporeal circula - tion, to the anterior descending coronary artery. We discuss the initial management, given the seriousness of the case.